RUSSIA. THE BACKGROUND OF THE RUSSIAN INVASION OF UKRAINE - HANAPPI, Hardy (Theoretical and Practical Research in Economic Fields, 2022)
This paper presents an interpretation of the underlying dynamics of global political economy, which has led to the invasion of Ukraine by Russia in February 2022. It thus is an alternative to interpretations that view the individual psychological traits of Vladimir Putin as the driving force behind this event. To enable a more sensible account, it turns out to be necessary to go back in the history of the conflict between Russia and NATO to the times of the Cold War. Briefly, two important fields of methodology – a theory of power and game theory – have to be touched upon. Finally, the justified emotional disgust concerning Putin’s aggressive war and the somewhat more detached scientific analysis are tried to be reconciled in the concluding paragraphs.